Output control of continuous-time uncertain switched linear systems via switched static output feedback - Carniato, Leonardo Ataide; Carniato, Alexandre Ataide; Teixeira, Marcelo Carvalho Minhoto; Cardim, Rodrigo; Mainardi Junior, Edson Italo; Assunção, Edvaldo (Taylor & Francis, 2018)
This paper is devoted to the robust (Formula presented.) and guaranteed cost control problems for continuous-time switched linear systems with polytopic uncertainties, considering an output-dependent switching law and a switched static output feedback controller. The proposed method offers new sufficient conditions based on Linear Matrix Inequalities (LMIs) for designing the switching strategy. In order to provide extra free dimensions in the solution space, some conditions become a special class of Bilinear Matrix Inequalities (BMIs). Therefore, the hybrid algorithm Differential Evolution–Linear Matrix Inequality is proposed for obtaining feasible solutions of this NP-hard problem. Theoretical analyses and numerical examples show that these new procedures reduce the design conservatism of two recent known methods for solving the presented control problems. Besides, a practical application of the method in the design and simulation of a robust switched controller of a switched semi-active suspension is performed.
Keywords: linear matrix inequalities; robust control; Robust output switching strategy; robust static output feedback (Formula presented.) control; switched static output feedback